2012
DOI: 10.1021/cm3021287
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ga3+ and Cu2+ in the High Interstitial Oxide-Ion Diffusivity of Pr2NiO4-Based Oxides: Design Concept of Interstitial Ion Conductors through the Higher-Valence d10 Dopant and Jahn–Teller Effect

Abstract: We have investigated the crystal structure, nuclearand electron-density distributions, electronic structure, and oxygen p er m ea t io n r a t e o f t h r e e K 2 N i F 4 -t y p e o x i d e s o f Pr 2 (Ni 0.75 Cu 0.25 ) 0.95 Ga 0.05 O 4+δ , Pr 2 Ni 0.75 Cu 0.25 O 4+δ , and Sr 2 Ti 0.9 Co 0.1 O 4−ε , in order to study the role of d 10 Ga 3+ , Jahn− Teller Cu 2+ , and interstitial oxygen O3 in the high oxygen diffusivity of Pr 2 (Ni 0.75 Cu 0.25 ) 0.95 Ga 0.05 O 4+δ . The composition Pr 2 (Ni 0.75 Cu 0.25 ) 0.95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 45 publications
8
70
0
Order By: Relevance
“…Considering the Xray diffraction patterns, the crystal structure of this phase may change from a triclinic to a tetragonal lattice at x = 0.05 and 0.1. A similar phase change has been reported in the case of Nd 2 NiO 4 ; the phase change was also detected in this study from the sharpness of the main diffraction peaks [24,25]. Figure 3 shows the oxygen permeation rate from air to He in Pr 2¹X Ni 0.76¹X Cu 0.24 Ga X O 4+¤ with La 0.1 Sr 0.9 Co 0.8 Fe 0.2 O 3 -(LSCF1982) catalyst as a function of X value.…”
Section: Effects Of Dopant On Oxide Ion Conductivity In Pr 2 Nio 4 2)supporting
confidence: 91%
See 1 more Smart Citation
“…Considering the Xray diffraction patterns, the crystal structure of this phase may change from a triclinic to a tetragonal lattice at x = 0.05 and 0.1. A similar phase change has been reported in the case of Nd 2 NiO 4 ; the phase change was also detected in this study from the sharpness of the main diffraction peaks [24,25]. Figure 3 shows the oxygen permeation rate from air to He in Pr 2¹X Ni 0.76¹X Cu 0.24 Ga X O 4+¤ with La 0.1 Sr 0.9 Co 0.8 Fe 0.2 O 3 -(LSCF1982) catalyst as a function of X value.…”
Section: Effects Of Dopant On Oxide Ion Conductivity In Pr 2 Nio 4 2)supporting
confidence: 91%
“…This small P O2 dependence of total conductivity in bulk sample might be explained by saturated amount of O i 00 , or the decreased mobility or trapping hole at the extremely large hole concentration in PNCG. It was reported that PNCG shows high oxide ion conductivity by interstitial oxygen in a rock salt block 5), 24) and so improved hole concentration suggests that the oxide ion conductivity is also improved by increasing the interstitial oxygen amount. Since the estimated activation energy for hole formation is almost the same with that of bulk sample, introduction of interstitial oxygen is expected and the oxidation state of Pr or Ni might be varied in the film because of a tensile strain, which is suggested by the expanded lattice parameter.…”
Section: ¹2mentioning
confidence: 99%
“…[ 333 ] Yashima et al explored the role of Cu 2+ and Ga 3+ in a Pr 2 NiO 4 -based oxide in depth. [ 185 ] The Cu 2+ introduced the Jahn-Teller effect into the crystal, which could stabilize the tetragonal structure of the material at high temperature and made the mobility of apical oxygen, which participated in the diffusion of oxygen in the lattice bulk. The higher symmetry of the tetragonal I 4/ mmm PLNCG is a factor of the lower activation energy for oxygen permeation rate, compared to the lower symmetry of the orthorhombic Bmab Pr 2 NiO 4+ δ .…”
Section: Ruddlesden-popper-type Metal Oxidesmentioning
confidence: 99%
“…PNO based cathodes on CGO [24] have been reported to yield R P as low as 0.08 Ω • cm 2 at 600°C (although more recent reports by the same group give a value of 0.28 Ω•cm 2 ) [14]; these relatively low resistances are somewhat surprising given that the nickelate is unstable and may react with the electrolyte as suggested by the appearance of NiO peaks in X-ray [14]. Substitution of Sr [26], La, Cu or Ga [27,28] in Pr 2 NiO 4 has been shown to improve stability, polarization resistance, and oxygen diffusivity.…”
Section: Introductionmentioning
confidence: 98%